EMAHAMAN POLIGAMI PADA FILM PEREMPUAN BERKALUNG SORBAN TINJAUAN MORALITAS FEMINISME - Ayunda Cindy Riani; Mawar Rahayu Putri; Tri Ratna Herawati (UNIB Press, 2026)
This study discusses gender inequality, the practice of polygamy in a patriarchal system, and the psychological conflict of female characters in the film Perempuan Berkalung Sorban. The purpose of this study is to analyze the elements of feminism, the representation of polygamy from a sociological perspective, and the dynamics of Annisa's personality based on Freud's psychoanalytic theory. The method used in this study is descriptive qualitative with content analysis through literature study, examining data in the form of dialogue, scenes, and narratives in the film. The results of the analysis show gender inequality reflected through women's restrictions in the fields of education, domestic roles, and the right to express themselves; polygamy is depicted as a practice that strengthens male dominance and has a psychological impact on women; and the conflict between the id, ego, and superego in the character Annisa reflects the inner struggle in facing patriarchal oppression. In conclusion, this film conveys a critique of patriarchal culture while emphasizing the importance of women's struggle to achieve justice and freedom in a restrictive social structure.